Training load insights into the elite junior Australian footballer using GPS and HR technologies - Henderson, B.; Cook, J.; Kidgell, D.; Gastin, P. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Physical activity information on the elite junior Australian football (EJAF) player is still under-explored, especially in the area of training load. With the aid of wearable athlete device technologies encompassing global positioning system (GPS) and heart rate (HR) sensors, accurate measures of training load can now be obtained. Methods: This investigation examined the training loads within the elite junior AF player across the in season period. Objective measures of physical load were obtained via individual GPS time motion analysis and HR. A total of 187 training session files were collected from three clubs across 19 training sessions within the 2009 TAC Cup competition season. Descriptive analysis of the key summary variables was undertaken to ascertain an accurate account of training load. Results: Summary GPS data revealed that the mean duration of training was 87 min. The mean distance covered by EJAF players was 6.0 km a training session. Further breakdown showed that low intensity activity (0-14.4 km/h) predominated with a mean distance of 4.5 km and high intensity running (above 14.4 km/h) contributed 1.5 km. A distance of 71.3 m/min was covered by players within a session. HR data revealed that players were exposed to an internal load relative to 70% of their predicted HRmax across the duration of training. Players spent on average, 21 minutes between 80-90% of their predicted HRmax. Session HRpeak of 190 bpm indicated that a player was exposed to a relative internal load between 90-95% of their predicted HRmax value at least once within a training session. Discussion: As this is the first investigation to assess the typical physical training load exposure of the EJAF using GPS and HR technologies, there is limited data to compare the present results against. Further investigations using GPS and HR technology to serially monitor EJAF across the annual periodisation cycle will enable a better understanding of the current training practices and physical load exposure of this cohort. Furthermore, accurate monitoring of training loads has the potential to minimise the risk of injury, burnout and overtraining of elite junior athletes. This could possibly lead to improved performance and enhanced participation longevity across the career of an athlete (Hartwig, Naughton et al. 2009).